Representation Nostalgia on Film Dilan 1990 - Mahalia Sri Lingga (Universitas Bunda Mulia, 2022)
Dilan 1990, the movie described about the nostalgic era of 90s which filmed on the life of teenage love story. This film has reached up to 6.315.664 viewers and rewarded as the best-selling film in 2018. This 90s teen love story tells of Dilan's struggle in the long process of going through challenges in order to get Milea to become a lover his heart. The conditions of the 90s which were limited in technology, space and time showed a striking difference from the current conditions in communicating, interacting as well as in the principles of the love struggle adopted by youth at that time. According to the data and also record from social media, this film was dominated by teenage fans. Interestingly, the fact that the movie was being watched by mostly teenagers who in fact did not live that era. Therefore, departing from this reality, the writer captures that the construction of past love stories or nostalgia is a interesting and accepted story for the minlenial generation. Furthermore this study uses a descriptive qualitative method with a representation theory approach. This study describes the elements of exotic nostalgia in the discourse of the 1990 film Dilan. Keywords: Dilan 1990 film, nostalgia, representation